How Discrete Positive Emotions Promote Pro-Environmental Behavior: A Systematic Review - Fareta Angelica Ichwana P; Gumgum Gumelar Fajar Rakhman; Ratna Dyah Suryaratri; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This study aims to systematically review the empirical literature on the role of positive emotions in encouraging pro-environmental behavior (PEB). Through the systematic literature review method, as many as 10 selected articles published between 2015–2025 were analyzed based on certain criteria, such as focus on specific positive emotions and relevance to pro-environmental actions. The results of the study showed that emotions such as anticipated pride, satisfaction, subjective happiness, compassion, and connection with nature had a significant influence on increasing individual intentions and involvement in pro-environmental actions. These emotions also act as mediators between other psychological factors, such as social norms, self-efficacy, and personal values, and actual behavior. This study highlights that positive emotions-based approaches are more effective and sustainable than approaches that emphasize guilt or fear. These findings contribute to the development of more empowering environmental communication and education strategies and support consistent eco-friendly behaviors.